The legal challenge of universal dark skies protection. Some comments on opportunities and limitations (Discourse of Law and Administration, 2023)
In public discourse, dark skies have long been considered as a common heritage of humanitythat is being lost due to uncontrolled, excessive, and harmful artificial light emissions. Thepurpose of this paper is to identify an international model for the legal protection of dark skies. Thequalification of the dark skies as a separate element of legal protection is problematic, because of theimpossibility of defining its boundaries and territorial affiliation. However, the dark skies can be treatedas a unique element of the cultural, natural (or mixed) landscape, which creates the identity of a site,giving it an outstanding universal value. The normative analysis included: The Convention Concerningthe Protection of the World Cultural and Natural Heritage, the European Landscape Convention,and resolutions of international organizations whose mission is to protect dark skies. In addition,the paper considers the source of the human right to dark skies as an inalienable human right, whichgrows out of the right to a clean environment.
Keywords: dark skies protection; artificial light pollution; dark skies heritage